A nanobody-based method for tracking factor XII activation in plasma - de Maat, Steven; van Dooremalen, Sanne; Groot, Philip G.; Maas, Coen (Thrombosis and Haemostasis, 2013)
The physiological role of the plasma protein factor XII (FXII), as well as its involvement in human pathology, is poorly understood. While FXII is implicated in thrombotic pathology as a coagulation factor, it can contribute to inflammatory conditions without triggering coagulation. We recently generated nanobodies against the catalytic domain of activated FXII (FXIIa). Here, we describe two of these nanobodies, A10 and B7, both of which do not recognise FXII. Nanobody A10 recognises the catalytic domain of purified β-FXIIa (80 kDa), but not that of purified α-FXIIa (28 kDa), whereas nanobody B7 recognises both. This suggests minute differences in the catalytic domain between these isoforms of FXIIa. The detection of FXIIa by these nanobodies in plasma can become compromised through inactivation by serine protease inhibitors. This effect can be efficiently countered through the addition of the small-molecular protease inhibitor PPACK. Finally, we show that our nanobody-based assays in vitro distinguish various activation products of FXII that differ with the type of activator present: whereas procoagulant activators solely trigger the formation of a species that is captured by B7, proinflammatory activators first generate a species that is recognised by B7, which is later converted into a species that is recognised by A10. These findings suggest that a progressive proteolysis of FXIIa results in the generation a non-procoagulant form of FXIIa, whereas retention of intermediate forms triggers coagulation. Moreover, our findings indicate the development of nanobodies against activated enzymes offers improved opportunities to investigate their contribution to health and disease.
Keywords: Plasma contact system; factor XII; bradykinin; nanobody; thrombosis; kallikrein-kinin system